Risk Management in Magnetic Resonance: Failure Mode, Effects, and Criticality Analysis. (19th September 2013) - Petrillo, Antonella; Fusco, Roberta; Granata, Vincenza; Filice, Salvatore; Raiano, Nicola; Amato, Daniela Maria; Zirpoli, Maria; di Finizio, Alessandro; Sansone, Mario; Russo, Anna; Covelli, Eugenio Maria; Pedicini, Tonino; et al.
Abstract : The aim of the study was to perform a risk management procedure in "Magnetic Resonance Examination" process in order to identify the critical phases and sources of radiological errors and to identify potential improvement projects including procedures, tests, and checks to reduce the error occurrence risk. In this study we used the proactive analysis "Failure Mode Effects Criticality Analysis, " a qualitative and quantitative risk management procedure; has calculated Priority Risk Index (PRI) for each activity of the process; have identified, on the PRI basis, the most critical activities and, for them, have defined improvement projects; and have recalculated the PRI after implementation of improvement projects for each activity. Time stop and audits are performed in order to control the new procedures. The results showed that the most critical tasks of "Magnetic Resonance Examination" process were the reception of the patient, the patient schedule drafting, the closing examination, and the organization of activities. Four improvement projects have been defined and executed. PRI evaluation after improvement projects implementation has shown that the risk decreased significantly following the implementation of procedures and controls defined in improvement projects, resulting in a reduction of the PRI between 43% and 100%.